2007
DOI: 10.1007/978-3-540-73817-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Based Filtering for Stochastic Inventory Control

Abstract: Abstract. An interesting class of production/inventory control problems considers a single product and a single stocking location, given a stochastic demand with a known non-stationary probability distribution. Under a widely-used control policy for this type of inventory system, the objective is to find the optimal number of replenishments, their timings and their respective order-up-to-levels that meet customer demands to a required service level. We extend a known CP approach for this problem using a cost-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…We retain their model and we augment such a model with three cost-based filtering methods to enhance domain pruning. One of these techniques, based on a relaxation proposed by Tarim [18] and solved by means of dynamic programming, has been already presented in [19]. In this work we provide two additional cost-based filtering techniques and we extend the discussion on Tarim's relaxation and on the implementation of the respective cost-based filtering method.…”
Section: Introductionmentioning
confidence: 99%
“…We retain their model and we augment such a model with three cost-based filtering methods to enhance domain pruning. One of these techniques, based on a relaxation proposed by Tarim [18] and solved by means of dynamic programming, has been already presented in [19]. In this work we provide two additional cost-based filtering techniques and we extend the discussion on Tarim's relaxation and on the implementation of the respective cost-based filtering method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it is possible to incorporate in our CP model dedicated cost-based filtering methods [15] based on a dynamic programming relaxation [5] that is able to generate good bounds during the search. Such a technique has been already employed under a service level constraint [1] and preliminary results in this direction under a penalty cost suggest that our exact CP model, when enhanced with these dedicated filtering techniques, is able to produce an optimal solution for instances up to 50 periods and more in a few seconds.…”
Section: Comparison Of the Cp And Mip Approachesmentioning
confidence: 93%
“…In this paper it was shown that not only CP is able to provide a more compact formulation than the MIP one, but that it is also able to perform faster and to take advantage of dedicated pre-processing techniques that reduce the size of decision variable domains. Moreover dedicated cost-based filtering techniques were proposed in [1] for the same model, these techniques are able to improve performances of several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Tarim and Smith [30] introduced a more compact and efficient CP formulation for the same model. Dedicated cost-based filtering techniques for such a CP model were presented in [31] and [32]. This latter enhanced model proved to be able to solve real world problem instances considering up to a 50 periods planning horizon in a few seconds.…”
Section: Existing Approachesmentioning
confidence: 99%
“…For a detailed discussion on this CP model see [31]. Each decision variableĨ t represents the expected inventory level at the end of period t. It should be noted that the expected inventory level at the beginning of such a period is simplyĨ t +d t and if a replenishment is scheduled in t this latter value denotes the order-up-to-level (S n ) in period t. Eachd t represents the expected demand in a given period t according to its probability mass function g t (d t ).…”
Section: Tarim and Kingsman's Approachmentioning
confidence: 99%